PENINGKATAN HASIL BELAJAR PENGETAHUAN TARI MENGGUNAKAN METODE COURSE REVIEW HORAY SISWA KELAS VII-F SMP NEGERI 148 JAKARTA - Larasati, Nadya (Program Studi Pendidikan Tari FBS UNJ, 2020)
The results of learning dance are an important part of dance learning activities. The results of students 'dance knowledge learning show the extent to which students' understanding and insight into dance knowledge. Various kinds of learning methods are applied to achieve maximum learning outcomes, one of which is the application of the course review horay method. The purpose of this study was to analyze the process and results of the application of the course review horay method to improve the learning outcomes of the 7th grade students of junior high school dance knowledge in Jakarta. This study used a Classroom Action Research method which was conducted in two cycles, with each cycle having 4 steps, consisting of planning, implementation, observation, and reflection. Data collection techniques through questionnaires, tests, interviews, and observations. The qualitative data analysis technique used the Miles & Haberman model with the stages of data reduction, data presentation, and conclusion drawing. While the quantitative analysis uses descriptive statistics. The results of the study showed that student learning outcomes increased with an average value in the first cycle of cognitive abilities that was 62.78 (55.56%), and the second cycle obtained an average value of 75.97 (77.78). Based on the results of the study, it can be concluded that the learning outcomes of dance knowledge can be increased by applying the course review horay method. The implication of this research is that the learning outcomes of dance knowledge can be influenced by other factors so that the next research can be continued by using other factors that can improve the learning outcomes of dance knowledge.